Nephron Sparing Surgery for Small Renal Mass at a University Teaching Hospital: A Six Years Retrospective Review - Rai, Bipendra DK; Poudyal, Sujeet; Dhital, Pawan; Pradhan, Manish; Chapagain, Suman; Luitel, Bhoj R; Chalise, Pawan Raj; Sharma, Uttam K; Gyawali, Prem R (Journal of Institute of Medicine Nepal, 2019)
Introduction: Nephron-sparing surgery (NSS) is the standard of care for clinical T1 (cT1), renal mass less than 7 cm, whenever intervention is indicated. It has ontological outcome equivalent to radical nephrectomy in small renal masses and it also minimizes the progression to chronic kidney disease. However, there is paucity of data on outcomes of NSS in Nepalese population. Methods: A six years retrospective review of medical records of patients undergoing partial nephrectomy from Jan 2012 to Dec 2017 in Department of Urology and Kidney Transplant Surgery at Tribhuvan University Teaching Hospital was done to determine its demographics and outcomes. Results: Twenty eight patients underwent nephron sparing surgery for clinical T1 renal masses in the past six years. Complications occurred in three cases. Five of the lesions were benign and 23 malignant on final histology. Clear cell carcinoma was the commonest variant of renal cell cancer. Margin was positive in two cases and both were kept in close surveillance. There was no local recurrence and renal impairment during five to 60 months follow up. Conclusion: Nephron sparing surgery is a safe procedure with good oncological outcome for clinical T1 renal mass. It prevents unnecessary nephrectomy in benign lesions as well as chronic renal impairment at the same time.